Interacting Timescales in Perspective-Taking - Dale, Rick; Galati, Alexia; Alviar, Camila; Contreras Kallens, Pablo; Ramirez-Aristizabal, Adolfo G.; Tabatabaeian, Maryam; Vinson, David W. (Frontiers in Psychology, 2018)
Through theoretical discussion, literature review, and a computational model, this paper poses a challenge to the notion that perspective-taking involves a fixed architecture in which particular processes have priority. For example, considerable work has shown that egocentric perspectives can arise more quickly, with other perspectives (such as of task partners) emerging only secondarily. This theoretical dichotomy is challenged here, and we propose a general view of perspective-taking as an emergent phenomenon governed by the interplay among several cognitive mechanisms. We first describe the pervasive relevance of perspective-taking to cognitive science. A dynamical systems model is then introduced which explicitly formulates the timescale interaction proposed. Implications are discussed, with ideas for future empirical research.